Oracle discoverer 10g handbook - Armstrong-Smith, Michael; Armstrong-Smith, Darlene (McGraw-Hill, 2006)
Generate detailed reports that will give your company the competitive edge Put essential information in the hands of end-users across your organization using Oracle Business Intelligence Discoverer 10 g and the comprehensive information contained in this Oracle Press guide. You'll learn, step-by-step, how to query databases and warehouses, format the results, and distribute dynamic, Web-enabled reports. All features are covered in full detail, including OracleBI Discoverer Desktop, Workbook Wizard, Plus, Viewer, Discoverer Administrator, Portlet Provider, OLAP, and Enterprise Manager. Real-world case studies and tutorials illustrate all of the analysis, security, and reporting capabilities of Oracle Discoverer 10 g . Set up, configure, and manage Oracle Business Intelligence Discoverer 10 g Perform ad hoc and fixed queries using the Workbook Wizard Integrate sorts, calculations, percentages, and parameters using Discoverer Plus Create reports with graphs, tables, titles, headers, footers, and margins Use Discoverer Viewer to review, format, export, email, and print reports Refine queries using interactive pivoting, drilling, and Hyper Drilling Control OLAP workbooks using the Discoverer Catalog and Oracle Enterprise Manager Establish access and sharing rights, and scheduling privileges with Discoverer Administrator Set up and use Portal using Discoverer Portlet Provider and Portlets Implement query shortcuts, cascading parameters and advanced analytic calculations using templates.